Towards Understanding The Protein Structure And Its Problems: Selecting Data Sources And Data Representation. - Sallim, Jamaludin; Abdul Hamid, Roslina; Abdullah, Rosni; Khader, Ahmad Tajudin (2007)
This paper aims to provide a basic idea for bio informatics researchers in gearing their works on protein structure. We will discuss generally on the protein structure, accessing the data and represent them with using selected visualization tools. The major problems of protein structure analysis also being highlighted.